2020
DOI: 10.1039/d0nj03752d
|View full text |Cite
|
Sign up to set email alerts
|

Selective detection and removal of picric acid by C2N surface from a mixture of nitro-explosives

Abstract: Nitro-explosives are a severe threat to the environment; therefore, detection and removal of nitro-explosives is the need of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Based on these analyses, it may be concluded that these three molecules are all physisorbed on the diazine monolayer. To clarify the physisorption of molecules on the monolayer, we also investigated the electron localization function (ELF), which is an efficient method to understand the features of chemical bonding, the lone electron pairs (nonbonding electron pairs), and (non)­covalent interactions between the molecules and the monolayer, and the results of the analysis of the characteristics of chemical bonding for the molecule adsorption system are similar to those of the noncovalent interactions analysis. , The ELF function has values between 0 and 1, which represents delocalization and the perfect localization features of the covalent bonding or the lone electron pairs, respectively. The ELF plots for the adsorption of the considered three molecules are presented in Figure a–c.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these analyses, it may be concluded that these three molecules are all physisorbed on the diazine monolayer. To clarify the physisorption of molecules on the monolayer, we also investigated the electron localization function (ELF), which is an efficient method to understand the features of chemical bonding, the lone electron pairs (nonbonding electron pairs), and (non)­covalent interactions between the molecules and the monolayer, and the results of the analysis of the characteristics of chemical bonding for the molecule adsorption system are similar to those of the noncovalent interactions analysis. , The ELF function has values between 0 and 1, which represents delocalization and the perfect localization features of the covalent bonding or the lone electron pairs, respectively. The ELF plots for the adsorption of the considered three molecules are presented in Figure a–c.…”
Section: Resultsmentioning
confidence: 99%
“…In the most stable structure of the diazine monolayer, the C and N atoms have similar bonding characteristics with the C 2 N monolayer, which is composed of two benzene rings bridged by pyrazine rings in which two nitrogen atoms face each other, ,, and the structural difference between the diazine and C 2 N monolayers is that one C atom binds to a H atom and thereby forms sp 2 hybridization in the diazine monolayer. As reported in a previous work, as the diazine monolayer has advantages such as ultrahigh specific surface area and semiconducting properties with wide band-gap width, it is expected that the diazine monolayer, which would be similar to the C–N 2D nanomaterials, , has promising potential applications in ion batteries, (photo-) catalysts, gas capture and storage, gas sensors, and so on. More interestingly, it had been demonstrated that the C 2 N monolayer as a gas sensor has excellent gas-sensing properties such as high sensitivity and selectivity for detection of gaseous pollutants. ,, The fact that the analogous structure C 2 N is a good candidate for a gas sensor indicates that the diazine monolayer can be expected to show excellent gas-sensing performance.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…[5][6][7] Industrially, picric acid is especially hazardous because it is volatile and slowly sublimes even at room temperature. So, the removal of picric acid from aqueous solutions has been a major focus of research and is vital.Up to now, various methods for instance, degradation, [8] oxidative destruction, [9] solvent extraction, [10] biodegradation, [11] electrochemical, [12] and adsorption [13] were applied to remove picric acid. In the middle of these methods, adsorption process has been recognized as one of the major methods for picric acid removal since this process is commonly easy to handle, cost effectiveness, high efficiency,…”
mentioning
confidence: 99%
“…Up to now, various methods for instance, degradation, [8] oxidative destruction, [9] solvent extraction, [10] biodegradation, [11] electrochemical, [12] and adsorption [13] were applied to remove picric acid. In the middle of these methods, adsorption process has been recognized as one of the major methods for picric acid removal since this process is commonly easy to handle, cost effectiveness, high efficiency,…”
mentioning
confidence: 99%